2016
DOI: 10.1016/j.jphotobiol.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Multiple active site residues are important for photochemical efficiency in the light-activated enzyme protochlorophyllide oxidoreductase (POR)

Abstract: Protochlorophyllide oxidoreductase (POR) catalyzes the light-driven reduction of protochlorophyllide (Pchlide), an essential, regulatory step in chlorophyll biosynthesis. The unique requirement of the enzyme for light has provided the opportunity to investigate how light energy can be harnessed to power biological catalysis and enzyme dynamics. Excited state interactions between the Pchlide molecule and the protein are known to drive the subsequent reaction chemistry. However, the structural features of POR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 48 publications
4
58
0
Order By: Relevance
“…The higher expression of FeCH in leaves also was observed in the study, and this could be ascribed to the reduction of Chls in tobacco leaves under 28.5 °C. At the later steps of Chls biosynthesis in plants, POR catalyzes the conversion of Pchlide into Chlide, accompanying with the degradation of POR and the synthesis of Chls (Beale 1999 , 2005 ; Kim and Apel 2012 ; Talaat 2013 ; Menon et al 2016 ). In the present work, it was observed that 18.5 °C significantly reduced the expression of POR gene in tobacco leaves during 15–30 days (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher expression of FeCH in leaves also was observed in the study, and this could be ascribed to the reduction of Chls in tobacco leaves under 28.5 °C. At the later steps of Chls biosynthesis in plants, POR catalyzes the conversion of Pchlide into Chlide, accompanying with the degradation of POR and the synthesis of Chls (Beale 1999 , 2005 ; Kim and Apel 2012 ; Talaat 2013 ; Menon et al 2016 ). In the present work, it was observed that 18.5 °C significantly reduced the expression of POR gene in tobacco leaves during 15–30 days (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At the later steps of Chls biosynthesis, the light-dependent protochlorophyllide oxidoreductase (POR) catalyzes the reduction of protochlorophyllide (Pchlide) to chlorophyllide (Chlide). In the processes, the tripolymer of the POR-NADPH-Pchlide was disaggregated, and the Chlide was released accompany with the breakdown of POR (Apel et al 1980 ; Armstrong et al 1995 ; Holtorf and Apel 1996 ; Reinbothe et al 2010 ; Kim and Apel 2012 ; Talaat 2013 ; Menon et al 2016 ). Finally, Chlide was catalyzed by chlorophyll synthetase (CHL) and chlorophyllide a oxygenase (CAO), respectively, and then turned into Chl a and Chl b, respectively (Beale 1999 , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…1A) [18]. Although several residues important to photocatalysis are known [23][24][25], a structural basis for POR photocatalysis has emerged only recently. Crystal structures of cyanobacterial POR as the apo-enzyme and a NADPH-bound complex are known [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[15] The reduction of the C17=C18 double bond occurs in a sequential manner by trans-addition of a hydride and a proton along the double bond, [14,16] after excitation of the pchlide by light. [16][17] Actually, first a ternary complex of substrate, cofactor and enzyme forms, which acts as a photoreceptor during the reaction. Under illumination, an endergonic light-driven hydride transfer takes place from NADPH to the C17 position of the pchlide, whereby a charge-transfer complex is formed.…”
Section: Introductionmentioning
confidence: 99%
“…The exact influence of the cysteine residue within the catalytic mechanism is not fully understood, yet. [17,[20][21] In the last decade a few LPORs were mostly studied from the viewpoint of their photochemical mechanism, [16] especially the LPORs from Synechocystis sp. [14,22] and Thermosynechococcus elongatus [20] were investigated regarding their expression, kinetic parameters and reaction intermediates.…”
Section: Introductionmentioning
confidence: 99%